Zoos and aquaria: dark tourism or light fun? A post-humanist perspective - Yerbury, Rachel M. (Frontiers in Sustainable Tourism, 2023)
Non-human animals in the field of Dark Tourism (DT) is an area of recent discussion. While DT initially described tourist sites of human suffering and death, this field undoubtedly encompasses nonhuman malaise. Some activities are unmistakably DT experiences, like bullfighting and hunting, whereas zoos and aquaria are considered more ambiguous. Using Fennel's post-humanist prototype, animals in zoos and aquaria are highlighted as examples of dark tourism objects who endure pain, suffering and thwarted flourishing. It is argued that animal-based DT activities arise from anthropocentric domination narratives of human exceptionalism and entitlement. In the captive context, nature and nonhumans are conceptualized as “other”, extending the dominant, progress-driven misapprehensions of human-nature separation, allowing people to deny the true and far-reaching effects of human impacts on nonhumans and the earth. Dark tourists seek the artificial manifestations of the captive utopia of zoos and aquaria and the collusion provided, permitting the dismissal of animal rights, biodiversity loss and climate change. An alternative perspective of deep justice is offered, where the wellbeing, interests and rights of animals are inherently valued. Embracing this perspective would allow the rejection of captive-animal dark tourism sites such as zoos and aquaria and for the flourishing of all beings to be to be upheld.